Gate Dispatching in Tidal River Network Areas Based on EFDC Model - ZHANG Xianguo; WANG Huipeng; HUANG Miansong; ZHENG Lei; LIU Xiaofang (Renmin Zhujiang)
Hydrodynamic regulation is an important measure to control black and malodorous water bodies and create a good water environment and water ecology.For tidal river network areas,the key to the treatment of water environment problems is to control the hydrodynamics of gates and pumping stations to achieve running water circulation.This paper simulates the hydrodynamic dispatching of the water quality maintenance of the water system in the tidal river network area of Fuzhou.A hydrodynamic water quality model based on the Environmental Fluid Dynamics Code (EFDC) is constructed for the complex river network of Fuzhou to simulate the influence of gate and pump dispatching under different water quality goals and diversion conditions in the study area on changes in water quality of river channels.According to the simulations of the model,it is concluded that the use of tidal range for diversion can reduce the operation and maintenance costs but cannot maintain the water quality at an excellent level.The use of pumping stations for diversion can rapidly restore the water quality of river channels,but pumping stations in different locations can lead to different effects on the water quality,and thus adjustment is required according to the actual operation and maintenance goals.The simultaneous opening of the gates on the south side of the water system and the pumping stations can easily cause reciprocating flow of water in the central area of the river network and result in water body turbulence,which is not conducive to the restoration and maintenance of water quality.Therefore,they should not be opened at the same time during operation.The conclusions of this paper can provide references for the implementation of water quality maintenance and hydrodynamic control in tidal river network areas.